Joint UK societies' 2014 consensus statement on renal denervation for resistant hypertension. Issue 1 (27th November 2014) - Lobo, Melvin D; de Belder, Mark A; Cleveland, Trevor; Collier, David; Dasgupta, Indranil; Deanfield, John; Kapil, Vikas; Knight, Charles; Matson, Matthew; Moss, Jonathan; Paton, Julian F R; Poulter, Neil; et al.
Abstract : Resistant hypertension continues to pose a major challenge to clinicians worldwide and has serious implications for patients who are at increased risk of cardiovascular morbidity and mortality with this diagnosis. Pharmacological therapy for resistant hypertension follows guidelines-based regimens although there is surprisingly scant evidence for beneficial outcomes using additional drug treatment after three antihypertensives have failed to achieve target blood pressure. Recently there has been considerable interest in the use of endoluminal renal denervation as an interventional technique to achieve renal nerve ablation and lower blood pressure. Although initial clinical trials of renal denervation in patients with resistant hypertension demonstrated encouraging office blood pressure reduction, a large randomised control trial (Symplicity HTN-3) with a sham-control limb, failed to meet its primary efficacy end point. The trial however was subject to a number of flaws which must be taken into consideration in interpreting the final results. Moreover a substantial body of evidence from non-randomised smaller trials does suggest that renal denervation may have an important role in the management of hypertension and other disease states characterised by overactivation of the sympathetic nervous system. The Joint UK Societies does not recommend the use of renal denervation for treatment of resistant hypertension in routine clinical practice but remains committed to supporting research activity in this field. A number of research strategies are identified and much that can be improved upon to ensure better design and conduct of future randomised studies.